Improving the ability of high school students in learning biographical texts through PowToon media - Jimat Susilo; Rosaelly Andryani; Li Kunmei (Universitas Ahmad Dahlan, 2022)
Biographies are very important to be given to students so that the exemplary in the text can inspire and motivate students. The purpose of this study was to describe the increased abilities and activities of SMA N 2 Indramayu students in learning biographical texts through PowToon media. This study used a nonequivalent control group design. This design involved two groups, namely the trial group and the comparison group, namely class X MIPA 1 totaling 36 students and X MIPA 2 totaling 36 students. The research instruments used were tests (pretest and posttest), observation sheets, questionnaires and documentation. The data analysis technique uses the IBM SPSS 25 application program, namely the data normality test and the Wilcoxon test. The results of the study showed that there was a significant increase in student learning outcomes in the trial class through PowToon media compared to the comparison class. The average learning outcomes for the trial group reached 85.5, while the comparison group obtained a less significant increase compared to the trial class, which was 66. Based on the results of the Wilcoxon test, it was known that Asymp. Sig. (2-tailed) has a value of 0.000 <0.05 which means it is rejected and accepted. That is, there is a difference between learning outcomes in the final test of the pilot class and the comparison class.